Checkpoint inhibitor–induced autoimmune central nervous system disorder in patients with metastatic melanoma and Hodgkin's lymphoma. Issue 2 (10th March 2021) - Möhn, Nora; Sühs, Kurt‐Wolfram; Angela, Yenny; Stangel, Martin; Ivanyi, Philipp; Beutel, Gernot; Gutzmer, Ralf; Skripuletz, Thomas; Grimmelmann, Imke
Abstract: Objectives: Immune checkpoint inhibitor (ICI) therapy has revolutionized the management of multiple cancers with previously poor prognosis. Despite its efficacy the therapy is associated with a wide spectrum of immune‐related adverse events (irAEs) including neurological deficits ranging from peripheral neuropathy, myopathy, and myasthenic syndromes to encephalopathy or meningitis. Up to now, neurological irAEs, especially those with central nervous system (CNS) involvement, have been reported rather sporadically. Symptoms can be unspecific, which results in a diagnostic challenge. Methods: In the study at hand, we report 5 patients who presented with symptoms of the CNS during ICI therapy indicating autoimmune encephalitis. Results: Symptoms ranged from headache and hallucinations to symptoms of the brainstem to cerebellar syndrome. Radiological findings according to brain magnetic resonance imaging were unspecific, and analysis of autoantibodies remained negative in all cases. All patients underwent lumbar puncture, and examination of the cerebrospinal fluid revealed an elevated cell count, and thus an indication of inflammation, in 4 cases (80%). Consequently, all patients received high‐dose steroid treatment, and symptoms of all patients with elevated cerebrospinal fluid cell count significantly improved. Conclusions: We demonstrate that symptoms of immune checkpoint inhibitor–induced encephalitis can be unspecific, and radiological findings are often inconspicuous. Thus, cerebrospinal fluid analysis is the most important examination to achieve a correct diagnosis, which in turn is decisive for a rapid start of therapy. Abstract : Despite its efficacy, immune checkpoint inhibitor therapy is associated with a wide spectrum of immune‐related adverse events including neurological symptoms ranging from mild headache to severe cognitive alterations. In the study at hand, we report 5 patients who presented with central nervous system symptoms during immune checkpoint inhibitor therapy indicating autoimmune encephalitis. We demonstrate that symptoms of immune checkpoint inhibitor–induced encephalitis can be unspecific, and radiological findings are often inconspicuous. Thus, cerebrospinal fluid analysis is the most important examination to achieve a correct diagnosis, which in turn is decisive for a rapid start of therapy.